The lost history of liberalism : from ancient Rome to the twenty-first century - Rosenblatt, Helena, 1961- (Princeton University Press, 2018)
"The Lost History of Liberalism challenges our most basic assumptions about a political creed that has become a rallying cry - and a term of derision - in today's increasingly divided public square. Taking readers from ancient Rome to today, Helena Rosenblatt traces the evolution of the words "liberal" and "liberalism," revealing the heated debates that have taken place over their meaning. In this timely and provocative book, Rosenblatt debunks the popular myth of liberalism as a uniquely Anglo-American tradition centered on individual rights. It was only during the Cold War and America's growing world hegemony that liberalism was refashioned into an American ideology focused so strongly on individual freedoms."--Jacket